Addressing the Transfer-Pricing Problem in an Origin-Basis X Tax - David Bradford (Center for Economic Studies and ifo Institute (CESifo), 2003)
In a previous paper I described how the tax design called the X Tax would facilitate an international tax system free of many of the complexities and avoidance opportunities plaguing the existing international tax regime and also have neutrality properties generally deemed desirable. A choice must, however, be made between two basic treatments of transborder business transactions - the origin and destination principles. The destination-principle approach sidesteps the need to identify arm's length terms of transborder transactions between related business entities - the transfer-pricing problem. This serious problem remains in the origin-principle approach, which, however, presents fewer challenges of monitoring the flow of goods and services across borders, obviates what I call the tourism problem whereby people can reduce their taxes by consuming in a low-tax jurisdiction and, arguably most important, avoids transition effects associated with introduction of the tax and subsequent tax rate changes that occur in the destination approach. In this paper I explore possible special rules for transborder transactions between related parties in an origin-based system to eliminate the transferpricing problem.
Keywords: 330